Conservative treatment of chronic Achilles disruption: a case report - González-Murillo, Manuel; Rodrigo-Alonso, Ángeles; Figueiredo-González, Héctor; Salgado-Rodríguez, Ángel María; Mota-Blanco, Sergio Mario (Revista Colombiana de Ortopedia y Traumatología, 2016)
We report a case of a 64 years old-female patient with ruptured left Achilles tendon within 2 months of evolution that has gone unnoticed. By the application of a conservative treatment recovered complete and symmetrical functionality in 5 months after the injury. Evidence level IV.